Structural and Electrochemical Analysis of SmBa0.8Sr0.2Co2O5+? Cathode Oxide for IT-SOFCs - Subardi, Adi; Indra, Ade; Setiawan, Jan; Fu, Yen-Pei (International Journal of Integrated Engineering, 2023)
The double perovskite SmBa0.8Sr0.2Co2O5+Î´ (SBSC82) was prepared using a conventional technique and evaluated as solid oxide fuel cells (SOFCs) cathode material which operates at intermediate temperatures. The SBSC82 cathode powder was produced using the solid-state reaction technique and an alumina ball as a grinder. XRD was used to determine the cathode powder structure, and the microstructure was analyzed using SEM. The oxygen content (Î´) for the SBSC82 cathode was recorded by a thermogravimetric analyzer. Powder patterns and lattice parameters were detected using General Structure Analysis System (GSAS) software. The symmetrical cell was examined using a Voltalab PGZ 301 potentiostat. The Î´ of SBSC82 cathode reached 5.68, 5.43, and 5.22 at 400 oC, 600 oC, and 800 oC. It was found that SBSC82 oxide shows a simple perovskite-type structure with tetragonal P4/mmm. The polarization resistance (Rp) of the symmetrical cell with SDC|SBCS82|SDC configuration reached of 0.420 Î©cm2, 0.091 Î©cm2, and 0.041 Î©cm2 at 650 oC, 750 oC, and 850 oC, respectively. Single cell specimen achieves a power density of 377 mW/cm2 under humidified air/hydrogen.